ASSESSMENT OF THE NATURAL REGENERATION STATUS OF IRVINGIA GABONENSIS (BUSH MANGO) IN THE KWANO FOREST OF GASHAKA GUMTI NATIONAL PARK, NIGERIA - E B, FEBNTEH; P, YANI J (Innovare Journal of Agricultural Sciences, 2023)
The International Union for Conservation of Nature (IUCN) describes the bush mango (Irvingia gabonensis) species as currently listed in the “lower risk or near threatened” category of its red list and an important versatile tree species in the family Irvingiaceae. I. gabonensis regenerates through seeds and it produces seeds with good germination as such; its natural size in natural habitat is actively regenerating. The present study was conducted to assess the natural regeneration status of I. gabonensis in Kwano Forest of Gashaka Gumti National Park in Nigeria. Through the biophysical survey, the number of regenerants (seedling, saplings, poles, and adults) and trees per hectare (based on diameter classes) was assessed in the forest. The study revealed that there was an increasing trend of I. gabonensis seedlings with good regeneration status. While saplings and adults are fair in regeneration per hectare in Kwano forest, respectively. Furthermore, poles had poor regeneration potentials in the study area. Hence, collectively, there was an apparent diminishing of the natural regeneration trend of I. gabonensis trees among pole classes in the Kwano Forest as a result of constant invasion and disturbances of bush pigs feedings on the ripe fruits thereby creating a setback on regeneration trend. The information is a basis to conservationists toward preservation and sustainable use of the tree species. Hence, the need for concurrent development of possible and efficient alternative method of regeneration is necessary.